MULTI-FREQUENCY SEISMIC STUDY OF GAS HYDRATE-BEARING SEDIMENTS IN LAKE BAIKAL, SIBERIA - Vanneste M.; De Batist M.; Versteeg W.; Golmshtok A.; Kremlev A. (My University, 2001)
In this paper we present and discuss the frequency-dependent behaviour of the acoustic characteristics of methane hydrate-bearing sediments in Lake Baikal, Siberia. Five different types of seismic sources (airgun-array, two types of single airguns, watergun and sparker) are used, encompassing a frequency bandwidth from 10 up to 1000 Hz. On low-frequency airgun-array data, the base of the hydrate stability zone (HSZ) is observed as a high-amplitude bottom-simulating reflection (BSR) with reversed polarity. The amplitude and continuity of the BSR decrease or even disappear on medium- to high-frequency data, a feature explained in terms of vertical and horizontal resolution. The increasing reflection amplitude of the BSR with increasing offset, the calculated reflection coefficient of the BSR and the occurrence of enhanced reflections below the BSR suggest the presence of free gas below the HSZ. The observation of some enhanced reflections extending above the BSR may be interpreted as an indication for free gas co-existing with hydrates within the HSZ. Amplitude blanking above the BSR is highly variable while the BSR itself appears to act as a low-pass frequency filter for medium- to high-frequency data.New single-channel airgun profiles provide the first seismic information across the Baikal Drilling Project (BDP-97) deep drilling site, at which hydrate-bearing sediments were retrieved at about 200 m above the base of the local HSZ. At the drilling site there are no seismic characteristics indicative of the presence of hydrates. Combination of the drilling and seismic information has allowed us to make a rough estimation of the volume of hydrates and carbon stored in the sediments of Lake Baikal, which lead us to conclude that the Lake Baikal gas hydrate reservoirs do not form a prospective energy resource.